Lessons from private equity any company can use - Gadiesh, Orit. (Memo to the CEO., 2008)
Gadiesh and MacArthur use the concise, actionable format of a memo to lay out the five disciplines that private equity firms use to attain their edge. This could be your opportunity to build the results-driven culture that will put your firm on par with private equity.